2016
DOI: 10.1063/1.4947450
|View full text |Cite
|
Sign up to set email alerts
|

On the kinetics of dendritic sidebranching: A three dimensional phase field study

Abstract: The underlying mechanism for dendritic sidebranching was studied using 3-D phase field modeling. Results showed that in 3-D the requirement of applying the random thermal noise to induce dendritic sidebranching (i.e., normally the case for 2-D phase field simulations) was fully relaxed. The stretching of the secondary or higher order arms occurred spontaneously and symmetrically as the growth of the dendrite. With periodic external perturbation and if the stimulating frequency was lower than a critical value, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 34 publications
2
15
0
Order By: Relevance
“…The effect of periodic pressure on dendritic growth has been studied experimentally and numerically by using the phase field method [11][12][13][14][15] . Phase field method [16][17][18][19][20][21][22][23] is a powerful tool to study dendritic growth and sidebranching during pressurized solidification [14,15,[24][25][26] . Börzsönyi et al [14,15] studied the effect of pressure on melting point in phase field model, and found that oscillating pressure or heating can tune the frequency of dendritic sidebranching dramatically.…”
Section: Influence Of Periodic Pressure On Dendritic Morphology and Smentioning
confidence: 99%
See 4 more Smart Citations
“…The effect of periodic pressure on dendritic growth has been studied experimentally and numerically by using the phase field method [11][12][13][14][15] . Phase field method [16][17][18][19][20][21][22][23] is a powerful tool to study dendritic growth and sidebranching during pressurized solidification [14,15,[24][25][26] . Börzsönyi et al [14,15] studied the effect of pressure on melting point in phase field model, and found that oscillating pressure or heating can tune the frequency of dendritic sidebranching dramatically.…”
Section: Influence Of Periodic Pressure On Dendritic Morphology and Smentioning
confidence: 99%
“…Börzsönyi et al [14,15] studied the effect of pressure on melting point in phase field model, and found that oscillating pressure or heating can tune the frequency of dendritic sidebranching dramatically. The underlying mechanism for dendritic sidebranching has been explored by applying periodic pressures at different frequencies using 3-D phase field modeling [25] . It is revealed that if the frequency of pressure is lower than the critical value, both the tip velocity and the sidebranching would be completely synchronized with the perturbation.…”
Section: Influence Of Periodic Pressure On Dendritic Morphology and Smentioning
confidence: 99%
See 3 more Smart Citations